Epidemiological study of porcine teschovirus infection in pigs at Bareilly, Uttar Pradesh, India. Issue 1 (2nd January 2022) - John, J. K.; Das, T.; Sethi, M.; Kattoor, J.J.; Tomar, N.; Saikumar, G.
ABSTRACT: Porcine teschoviruses (PTVs) belong to the genus Teschovirus within the family Picornaviridae had 13 serotypes linked with a variety of clinical diseases. The objective of the present study was to detect the epidemiological data's of PTV in Bareilly district of Uttar Pradesh (UP), India. Different epidemiological parameters such as age, sex and seasonal changes from February 2015 to February 2016 were recorded. A total of 106 faecal/intestinal contents samples were screened for PTV infection using reverse transcription polymerase chain reaction (RT-PCR) assay. Based on the RT-PCR assay of the faecal/intestinal samples, 19.8% (21/106) samples were positive for PTV. Out of 21 positive cases, 11.1% (5/45) were necropsied animals, 32.5% (14/43) from faecal sample collected from swine production farm and 11.76% (2/17) were intestinal contents of slaughtered animal. Age-wise highest prevalence was found in nursery age group 32.6% (17/52) followed by adult age group 13.3% (4/30) and was absent in suckling piglets in the current study. Sex-wise prevalence was recorded higher in males, 25% (12/48), than in females, 15.51% (9/58). Seasonally, prevalence was highest in winter than in summer. Prevalence of PTV is more in healthy pigs than in diarrhoeic pigs. The observations of the present study would provide a basis for a further extensive epidemiological and pathogenicity studies of PTV circulating in swine population of India.